Toward a One-Roof System and an Independent Tax Court: Indonesia between the United States and Germany - Efendi Ibnususilo; Yassine Chami; Saminu Abacha Wakili; Faiqah Nur Azizah (Lembaga Contrarius Indonesia, 2026)
The research departs from a fundamental problem, the dual roof system that historically placed the Tax Court under divided supervision between the judiciary and the executive, particularly the Ministry of Finance, thereby creating structural ambiguity and potential conflicts of interest between tax collection and adjudication functions. This condition raised concerns regarding the judicial independence, accountability, and public trust in tax dispute resolution. Using a normative juridical method with statutory, conceptual, and comparative approaches, this study analyses constitutional provisions, statutory regulations, and institutional practices governing the Tax Court. The research finds that, first, the reform of Indonesia’s tax adjudication system reflects a constitutional imperative to secure genuine judicial independence by ending the dual roof structure and fully integrating the Tax Court under the authority of Supreme Court, as mandated by Decision No. 26/PUU-XXI/2023 of the Constitutional Court of the Republic of Indonesia. Second, comparative insights from the United States and Germany demonstrate that effective judicial independence in tax matters requires structural separation from fiscal authorities, hierarchical judicial review, professional specialisation, and administrative as well as financial autonomy. Moreover, procedural differentiation, digital transparency, and layered oversight mechanisms are essential to prevent conflicts of interest and ensure accountability within a unified judicial framework. Third, as a policy model, Indonesia should adopt a fully integrated one-roof tax court system supported by tiered appellate review, institutional autonomy, specialised judicial training, and comprehensive digital governance to guarantee an independent, transparent, and accountable tax judiciary.